Romanticism in James Horner’s Songs: If We Hold On Together, Somewhere out There, I Want to Spend My Lifetime Loving You: Expressive Approach - Yuliastuti, Anicleta; Purba, Paulus (Dinamika : Jurnal Sastra dan Budaya, 2016)
The topic of this study is about Romanticism of James Horner's songs that entitled If We Hold On Together, Somewhere Out There, I Want To Spend My Lifetime Loving You. The purpose of this study is to find out how James Horner expressed romanticism in his literary works. The theories used to analyze the data are expressive theory made by M.H Abrams and poetry theory from Persy Bysshe Shelly. The research design used is quantitative research. Data collection and analysis techniques by conducting intense readings and conducting content analysis. The research findings show that the romanticism in James Horner's song utilizes parallelism, hyperbole, personification, symbol, imagery, and antitheses. The romanticism expressed by James Horner in his song entitled If We Hold On Together, Somewhere Out There and I Want To Spend My Lifetime Loving You is to tell about the beauty of nature, emotions, feelings and intuitions that are poured out of the author through a message songs lyrics inspired by stories of movie imagination.